2014
DOI: 10.1007/s11060-014-1515-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes and genomic characteristics of single focus and multifocal glioblastoma

Abstract: We investigate the differences in molecular signature and clinical outcomes between multiple lesion glioblastoma (GBM) and single focus GBM in the modern treatment era. Between August 2000 and May 2010, 161 patients with GBM were treated with modern radiotherapy techniques. Of this group, 33 were considered to have multiple lesion GBM (25 multifocal and 8 multicentric). Patterns of failure, time to progression and overall survival were compared based on whether the tumor was considered a single focus or multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 19 publications
3
29
0
Order By: Relevance
“…Our data are in agreement with existing findings in that uGBMs and mGBMs tend to most frequently recur in-field, 14 although that publication found a PFS but not an OS difference, contrary to our findings. Moreover, we could also confirm the two most established therapy – independent prognostic factors age and KPS score – in the univariate and multivariate analyses.…”
Section: Discussionsupporting
confidence: 90%
“…Our data are in agreement with existing findings in that uGBMs and mGBMs tend to most frequently recur in-field, 14 although that publication found a PFS but not an OS difference, contrary to our findings. Moreover, we could also confirm the two most established therapy – independent prognostic factors age and KPS score – in the univariate and multivariate analyses.…”
Section: Discussionsupporting
confidence: 90%
“…No M-GBMs belonged to the G-CIMP subgroup. Paulsson et al [19] reported a similar classification trend in the eight M-GBMs among the 41 GBM patients in their study. In their cohort, five (63%) were of the mesenchymal subtype, and none were of the G-CIMP subtype.…”
Section: Discussionsupporting
confidence: 63%
“…Other clinical behaviors that may be affected include multifocality [20], the presence of satellite nodules [21], and the likelihood of pseudoprogression [22]. A major disadvantage of genomic analyses of GBM behavior is that they are generally underpowered studies because of the expense and availability of fresh frozen tissue in a tumor bank.…”
Section: Discussionmentioning
confidence: 99%